Results of expert evaluation of problems of organization of ambulatory-polyclinic assistance - E. A. Finchenko; I. V. Sharapov; O. I. Ivaninskiy; M. A. Sadovoj; L. S. Shalygina (Бюллетень сибирской медицины)
Introduction. An important role in health care management was taken by the service of managing the volume of medical care for this population group and the progressive development of the opportunities of the district doctor and GP for most of the population which requires only general medical assistance while maintaining all the possibilities for the consultant to get this patient’s advice.Materials and methods. An expert assessment of the organization’s problems, prospects for development and the main directions for optimizing the outpatient care were conducted among the heads of health authorities, state outpatient clinics and the oblast’s top specialists (111 experts).Results. An expert assessment of the problems and perspectives of the organization of out-patient and polyclinic care in the territorial polyclinics obtained the following results. At present, the health of the population is monitored by: citizens themselves – 23,1%; District doctors – 7,9%, medical specialists – 1,2%, no one follows – 67,8%. At the same time, according to experts, citizens themselves should monitor citizens’ health – 81,3% and district doctors – 18,7%. With a deterioration in health status or an exacerbation of the disease, patients most often turn to: the district doctor – 84,1%; The average medical worker working on the site – 2,7% and the specialist doctor – 13,2%. At the same time, according to experts, patients with worsening health or exacerbation of the disease most often need to contact the local doctor – 88,3% and the average medical worker working on the site – 11,7%.The share of unreasonable visits is: a district doctor – 28,1%, house calls – 56,4%, doctors-specialists – 37,3%. Thus, according to experts’ estimates, the share of unjustified visits of district doctors is 28,1%, of the doctor’s call at home – 56,4%, and of specialist doctors – 37,3%, which indicates a low level of organization of work of polyclinics. The proportion of visits by patients to district doctors that could be resolved: on pre-hospital admission, is 24,7%, by telephone consultation, is 24,5%. Thus, the share of visits to district doctors, which could be resolved at a pre-hospital reception and by telephone consultation, is almost half (49,2%).The proportion of visits by patients to medical specialists that could be resolved by telephone consultation: between the district doctor and medical specialists is 11,2%, the number of patients by telephone by medical specialists is 12,4%. Thus, the share of visits by specialist doctors, which could be resolved by telephone consultation between the district doctor and specialist doctors and patient consultations by telephone by specialist doctors, is almost a quarter of all visits (23,6%).Discussion. The data obtained are in some ways consistent with the results of a number of authors who are optimizing outpatient care in terms of the unreasonableness of visits, the possibility of transferring part of the functions of primary general medical reception to specially trained middle medical personnel, using telephone consultations between patients and between doctors, etc.Conclusion. The results of the expert assessment of the organization of outpatient care helped to identify some approaches to optimizing its delivery in the territorial polyclinics. This is optimization of the work of district doctors; Transfer of a certain part of the functions performed by district doctors to district nurses and paramedics; The development of a system for counseling patients and district doctors by medical specialists of polyclinics and other medical organizations.